Integrative taxonomy and DNA barcoding of Thai Caddisflies (Trichoptera), with the description of a new Species - Jaroenchaiwattanachote, Chavanut; Pramual, Pairot; Wangwasit, Khanit; Bunchalee, Pasakorn; Thanee, Isara (Zootaxa, 2025)
Caddisflies (Trichoptera) are abundant and diverse aquatic insects. Their immature stages inhabit a wide range of aquatic environments, making them ideal candidates for water quality biomonitoring. However, the limited morphological characteristics available for species identification in the immature stages pose a significant challenge to their application in biomonitoring. In this study, we evaluated the effectiveness of DNA barcoding, based on mitochondrial cytochrome c oxidase I (COI) sequences, for species identification of caddisflies in Thailand. A total of 1,487 adult specimens were collected and morphologically identified into 13 species across 8 genera and 4 families. From these taxa, 88 COI sequences were generated from representative specimens. Maximum intraspecific genetic divergence ranged from 0% to 3.08%. Only three species were successfully matched to COI sequences in the BOLD database, while nine species are reported here for the first time, and one species remained ambiguous. Integrating COI barcoding sequences with morphological data revealed that one species, morphologically similar to Triplectides indicus (Walker 1852), represents a novel species, Triplectides buengkanensis sp. nov. We provide a detailed description, illustrations, diagnostic features, and DNA barcoding sequences for this new species.